A luta encarnada: corpo, poder e resistência nas obras de Foucault e Reich - Barreto, André Valente de Barros (2007)
Considering the growing importance that the body is gaining in the contemporary world, our objective in this thesis is to question the relationship between body and power, subject that has thus far been scarcely explored from a political science point of view. For that, we will work predominantly with Michel Foucault s work, using systematic analysis of this outstanding author, pioneer in showing that the body is in the center of the relations of power. Despite bearing an important contribution to the subject, Foucault s work presents some problems, among which we point out embracing the concept of the body as excessively abstract. Echoing a difficult relationship that the human sciences have kept with the body in modern days, by either simply ignoring it or considering it only as a symbolic object, Foucault ultimately detaches the body from its biological traces; the body which, when assuming its materiality, does so under an exceedingly mechanicist perspective. We repute that this view of the body devitalizes the subject and weakens the very idea of resistance that the French philosopher sustains in his work, reason why we propose, through an interdisciplinary dialogue, the adoption of another view of the body. It is in the work of Wilhelm Reich, as well as in some contemporary biologists and neurobiologists, that we will find the elements to think of the body not as a mere compilation of inert, malleable parts, as proposed by biomedical knowledge, but as an especial materiality, alive and dynamic, which remits to a long evolutionary process, occupying a central spot in our so called superior life. Our hypothesis is that this living body, capable of contemplating both symbolic and social aspects, as well as biological and material aspects, can intensify Foucault s idea of resistance, making the work of composing the self more efficient in its task of elaborating internalized means, capable of eluding the modern mechanisms of power: the body as an important ally against the methods of domination